Paladins with Muscle Cramps: Immersion, MMORPG’s and Nozick’s Experience Machine (Analele Universității București.Filosofie, 2025)
When he first formulated the famous ‘Experience Machine’ thought experiment in 1974, Robert Nozick could only give his readers one analogy with a potential real-life ‘device’: psychoactive drugs. Now, decades later, MMORPG’s like World of Warcraft and EVE Online, with their promise of delivering immersive pleasure to their users, have been dubbed as experience machines. However, some have argued that MMORPG’s cannot be what Nozick had in mind when he developed his thought experiment for two reasons: because of the interaction between users mediated by avatars and because they lack sensory-immersion. We discuss how both arguments fail to address the necessary conditions for a truly Nozickian experience machine: (i) guaranteed immunity from any stimuli generated in the circumstances of the “real”, physical world and (ii) lack of awareness, while being plugged in an experience machine, of the actual source of an experience. Even though MMORPG’s cannot be experience machines in the sense of the original thought experiments, they might still provide an opportunity to address the original concerns that Nozick had regarding hedonism, or other, more recent (but closely related) as escapism through technology.